2022
DOI: 10.1186/s12985-022-01796-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome analysis of coxsackievirus B3 reflects its genetic diversity in China and worldwide

Abstract: Background Coxsackievirus B3 (CVB3) has emerged as an active pathogen in myocarditis, aseptic meningitis, hand, foot, and mouth disease (HFMD), and pancreatitis, and is a heavy burden on public health. However, CVB3 has not been systematically analyzed with regard to whole-genome diversity and recombination. Therefore, this study was undertaken to systematically examine the genetic characteristics of CVB3 based on its whole genome. Methods We combi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 61 publications
2
6
0
Order By: Relevance
“…29 Coxsackievirus B3 has a worldwide geographic distribution. 30 Coxsackievirus B3 is associated with myocarditis in addition to meningitis and most commonly infects infants, which coincides with the age group represented in this study (Median age of 3.5 months; supplementary table). 31 Three genotypes were detected from Enterovirus C species during this study.…”
Section: Discussionsupporting
confidence: 82%
“…29 Coxsackievirus B3 has a worldwide geographic distribution. 30 Coxsackievirus B3 is associated with myocarditis in addition to meningitis and most commonly infects infants, which coincides with the age group represented in this study (Median age of 3.5 months; supplementary table). 31 Three genotypes were detected from Enterovirus C species during this study.…”
Section: Discussionsupporting
confidence: 82%
“…Recombination affects virulence and the ability of the virus to spread in the nonstructural protein regions (P2 and P3) and may lead to outbreaks of this serotype ( 22 , 24 ). EV-B is more prone to recombination events and has been reported for serotypes E7, CVA9, CVB3, and CVB5 ( 6 , 25 27 ). The results of this study showed that the two E5 strains have high similarity with other serotypes in the nonstructural region, such as CVA9, E6, E11, and EV-B85, which were highly similar to the CVA9 and EV-B85 isolates in the Xinjiang and Tibetan regions of China in the 3C-3′UTR.…”
Section: Discussionmentioning
confidence: 93%
“…Coxsackievirus B3 (CVB3) is a pathogenic enterovirus belong to the genus Enterovirus of the family Picornaviridae . It is a common cause of aseptic meningitis, encephalitis, myocarditis, and acute flaccid paralysis and can lead to serious complications, especially in neonates and immunocompromised patients .…”
Section: Resultsmentioning
confidence: 99%